Differences in the practice of binding international law in Southeast Asian countries: How will it affect the stability of law enforcement? - Joseph, Antonio Marcos; Shivana, Nur; Shaiza, Layina (Faculty of Law, Universitas Negeri Semarang, 2022)
Differences in the practice of binding international law in a sovereign state have different forms which are based on various theories of international law. As a result, each country has different perceptions even in terms of law enforcement. The study uses the library research method where the author refers to legal journals and certain books as well as the opinions of experts. However, in practice, the author prefers to refer to journals and books, because the sources from journals and books can be accounted for. The author also cites sources that have been mentioned through footnotes or footnotes. This study aims to analyze different legal practices in binding international law in Southeast Asian countries and their impact on law enforcement.